UJI DIAGNOSIS KRITERIA McISAAC PADA FARINGITIS AKUT STREPTOKOKUS Î² HEMOLITIKUS GRUP A - , Imanuel Yulius Malino, Prof. dr. Sri Suparyati Soenarto, PhD, Sp.A(K) ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Early use of antibiotic in acute upper respiratory infections has become controversy because most are caused by viral infection. Appropriate strategy is needed todiagnoseacute pharyngitis so antibiotic usage will be more appropriate and reduce excessive antibiotic usage with all the consequences.This study aim to do diagnostic test for McIsaacCriteria in diagnosing Group-A Î²-hemolytic Streptococcus (GABHS) on children with acute pharyngitis. This was a crosssectional study, diagnostic test of clinical criteria with throat swabsculture as the gold standard. The research was conducted August 1 st , 2011 until February 6 th , 2012 on children 3-14 years oldatpediatric outpatient clinic and emergency wardat Sanglah Public Hospital and pediatric outpatient clinic at WangayaHospital. Five hundred and fifty cases with acute pharyngitis during the study period, 313 of them 3-14 years old, 199 children were excluded due to history of antibiotics in two weeks, 114 children who meet the inclusion and exclusion criteria are involved. GABHS prevalence in this study are 7.9%. McIsaacâs Area Under the Curve (AUC) from Receiver Operating Characteristic (ROC) curve is 78.1% with P = 0.005 (95% CI 60.3% to 96%). The optimal ROC cutoff for McIsaacscoreis greater than or equal to 4 which has 66.7%(95% CI 49% to 97%) of sensitivity, 87.6% (CI 95% 81% to 94%) of specificity, 31.6% (CI 95 % 11% to 52%) of positive predictive value (PPV), 96.8% (95% CI 93% to 100%)of negative predictive value (NPV),86.0%of accuracy, positive likelihood ratio (LR+) is 5.4 (95% CI 2.7 to 10.7) and negative likelihood ratio (LR-) is 0.4 (95% CI 0.2 to 0.9). McIsaac Criteria total scoreofless than four is favorable to exclude GABHS pharygitis diagnosis. Total score criteria McIsaac greter than or equal to four requiresfurther examination toconfirm GABHS pharyngitis.